(3TQM aUjM KYdHs - (3GHf OQSJhjg YHO Gddg Hf LYaQ GdfMhis; (3CHh GdYHGS CMeO Hf jMji Hf RjO KYdH GdTjHGfj Gdchaj GdfMhj,J (B291 (3g` s
(3ChdgG (B:s
(3GdPi HYKfG HYO MeO Gddg JYGdi Ydi JUMjM cJGH GdaUjM GdefShH Edi CMeO Hf jMji s
(3BNQgG (B:s
(3heMUhQkG cd Pdc HCHhGH eQJHI hCHfjI eeKdI haUhd eaUdI Jbje Ydi GdeMLI hJefY ef GdeVdI hHGddg GdMhd hGdbhI hdg GdWhd hGdefI s
(3Ydi GdhQbI GdChdi NW GdEeGe GdLhGdjbi ESeGYjd Hf ehghHs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B252s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs